Nutritional Ecology of the Ruminant - Van Van Soest, Peter J. (Book collections on Project MUSE., 1994)
This monumental text-reference places in clear persepctive the importance of nutritional assessments to the ecology and biology of ruminants and other nonruminant herbivorous mammals. Now extensively revised and significantly expanded, it reflects the ...